Effect of Maillard reaction conditions on physicochemical properties and oxidative stability of microencapsulated chia oil - Ixtaina, Vanesa Yanet (2019)
Chia seed oil presents a very high content of polyunsaturated fatty acids (PUFAs 60% omega-3 alfa-linolenic acid 18:3, 20% linoleic acid 18:2) which are very appreciated in terms of health and nutrition aspects. Clinical studies have reported beneficial effects on cardiovascular disease, immune functions, neurology disorders and inflammation. However, the main deteriorative process related to chia oil is the occurrence of lipid oxidation. Some techniques, such as microencapsulation, have been developed to provide protection to this type of oils. Many studies have demonstrated that Maillard reaction products (MRPs) have anti-oxidative properties. For this reason, these compounds could be used as wall material for oil microencapsulation. The objective of this research work was to characterize the physicochemical properties of microencapsulated chia seed oil MRPs, as wall material, obtained by the application of different heat treatments on the aqueous phase. Chia O/W emulsions were composed by NaCas, lactose, and chia oil (10, 15 % wt/wt). The aqueous phase was heated at different temperatures (60 and 100°C) for 30 min to promote the MRPs formation. Then, the microcapsules were obtained by spray-drying of the emulsions at 170/90°C inlet/oulet temperatures, respectively. Microencapsulation efficiency, moisture content, water activity and parameters associated with the oxidative stability were determined. All the systems showed a high microencapsulation efficiency (> 99%). The moisture content and water activity (aw25°C) of microcapsules ranged between 0.020-2.998 % (d.b.) and 0.243-0.470, respectively. These levels are in accordance with those required to the addition in dried foods. Regarding the oxidative stability, the accelerated oxidative test (Rancimat) and the peroxide values (PV) revealed a very significant influence of the heat treatment, with the highest induction time (ti) and the lowest PV for microcapsules obtained from emulsions constituted by 15% content oil and an aqueous phase submitted to a heat treatment of 100°C, 30 min. This information is very interesting to be considered and applied for the development of functional foods enriched with these essential fatty acids.